INFLUENCE OF ORGANIZATIONAL CULTURE, MOTIVATION AND SATISFACTION THROUGH COMMITMENT TO EMPLOYEE PERFORMANCE - Tehubijuluw Zacharias (BADATI, 2021)
This study aims to analyze the influence of organizational culture, motivation and job satisfaction through commitment to employee performance. This research is an explanatory research conducted for four months, from June to July 2021. The population is 303 people. The sampling technique is proportional stratified random sampling. Determination of the number of samples is based on the sample table developed by Issac and Michael, where if the population is 303 people, then at the 95% confidence level, the sample size is 189 people. Analysis of the data used is path analysis. The results showed that the variables of organizational culture, motivation and job satisfaction through organizational commitment together (simultaneously) had a positive and significant effect on the variable performance of the employees of the Education and Culture Office of Maluku Province.